(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2025)
The present article suggests a means to reconceptualize the chronotope in order to widen its application and rethink its generic relations to the individual text. Bakhtin singles out an overarching chronotope for every novelistic genre and subgenre, considered as historic essences. However, he also identifies a horizontal and a vertical dimension of the chronotope which may coexist in a narrative. By focusing on these dimensions, we may analyze individual narratives taken from different genres. In particular, the article shows just how noteworthy are the affinities between the vertical dimension of the chronotope, as outlined by Bakhtin himself, and an extensive theorization of the short story beginning with the German Romantics. The methodological shift thus advocates a study of the specific genericity of an individual text rather than to the insertion of the text into a broadly categorized genre.